Disenfranchisement, reenfranchisement, and crime - Uggen, Christopher J. (Democracy, governance, and law, 2025)
Purpose - This chapter reviews the evidence on disenfranchisement, reenfranchisement, and crime, while also challenging the notion that the franchise should be conditional on its capacity to prevent or control criminal behavior. Methodology/approach - First, we introduce the question of voting rights for people with felony convictions. We briefly review theories of crime and democratic participation and present evidence on the link between voting and subsequent crime. Second, we argue that the question itself is the problem and argue for severing the link between the right to vote and past or subsequent criminal behavior. Findings - Empirical research has not reached a firm consensus on the relationship between felony voting bans and subsequent crime, suggesting that strong causal claims are likely premature. But we also question the question, asking whether to view disenfranchisement through the lens of crime control or the lens of civic inclusion and democratic participation. Originality/value - This chapter challenges the notion that the franchise should rest upon its capacity to prevent or control crime.